Brand loyalty among mobile users - Ghimire, Mahima; Karki, Dipendra (NCC Journal, 2022)
The purpose of this study is to explore the factors that influence brand loyalty among young mobile phone users. The study establishes a conceptual framework and tests hypotheses with a sample of 315 respondents from mobile phone users of various brands to explore the factors influencing brand loyalty. A structured questionnaire is used to gather data, and a descriptive and causal-comparative research design is used to assess the impact of perceived brand quality, customer satisfaction, brand image, brand experience, and social media marketing on brand loyalty. The study reveals statistically significant positive correlations between the study variables and brand loyalty using both descriptive and inferential statistical techniques. Notably, perceived brand quality, customer satisfaction, brand image, brand experience, and social media marketing all have significant positive connections with brand loyalty, showing that improving these factors can lead to higher user loyalty. Regression analysis, on the other hand, shows that only perceived brand quality, customer satisfaction, and brand experience have a significant impact on brand loyalty. This result emphasizes the important roles of quality, customer satisfaction, and brand experience in developing long-term brand loyalty. These findings have implications for users, suppliers, and regulatory agencies, shaping strategies and approaches for developing long-term brand loyalty.